Preparation and characterization of liquid phase (55B2O3-45Bi2O3) sintered cobalt doped magnesium titanate for wideband stacked rectangular dielectric resonator antenna (RDRA) - Tripathi P.; Sahu B.; Singh S.P.; Parkash O.; Kumar D. (My University, 2025)
Cobalt doped magnesium titanate (MCT) was prepared by a solid state ceramic method. Phase formation was investigated using X-ray diffraction and Rietveld refinement methods. 55B2O3-45Bi2O3(wt%) glass was prepared by the melt quench method. 0, 1 and 3 wt% glass was added to lower the sintering temperature of MCT from 1250 °C to 1050 °C. Dielectric properties of cobalt doped magnesium titanate (MCT) sintered with glass were determined. Dielectric constant was measured using transmission line (rectangular waveguide) method at different microwave frequencies in X-band (8.5-12.0 GHz). It has been found that value of dielectric constant is reduced by increasing percentage of glass. Optimized dielectric properties of MCT were achieved for the case of 1% glass addition and sintering at 1000 °C for 2 h. This MCT composition was used in fabrication of stacked (with Teflon) rectangular dielectric resonator antenna (RDRA) using coaxial probe feed for excitation with good impedance matching and wideband performance. Effects of antenna parameters such as probe height and teflon height are investigated using Ansys High Frequency Structure Simulator (HFSS) software. The experimental results are in good agreement with simulated results. The proposed antenna provides the measured input impedance bandwidth of 38.6% (6.44-9.52 GHz) for reflection coefficient (S11) values less than -10 dB with a measured peak gain of 7.9 dB at 8.4 GHz. The broadside radiation patterns are obtained (for both E- and H-planes) in the useful frequency range with fairly low cross-polarization levels in E-plane. © 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.